Tom Trueheart and the Land of Dark Stories - Beck, Ian (Tom Trueheart, 2008)
Twelve-year-old Tom Trueheart, accompanied by his friend Jollity the crow, must journey to the dangerous Land of Dark Stories to rescue his brothers and their princess brides, and to try to defeat the villainous Ormestone once again.